The Effect of Applying Organic Compounds on the Amount of Lead, Nickel and Cadmium in Urban Sewage Sludge (Case Study: Sewage Sludge in Sari Refinery) - Mohammad Ali Bahmanyar; Seyed Mostafa Emadi; Mehdi Ghajar Sepanlou; Mehdi Hosseini (علوم محیطی)
Introduction: urban sewage sludge contains significant amounts of essential elements for plant growth, which can be optimally used in the agricultural process. However, the presence of heavy elements is one of the main limitations of the direct use of this substance in agricultural lands. Therefore, the general purpose of this study is to investigate the role of using organic modifiers (rice straw and branches from citrus pruning) in urban sewage sludge and converting them into compost and biochar in reducing the amount of heavy elements, and also the partial purpose of this study is to compare the effect of compost and biochar on reducing the amount of heavy elements. Material and Methods: This study was conducted in two separate designs in the form of a randomized complete block with 9 treatments and 3 replications. The first plan included the production of compost using the combination of urban sewage sludge with rice straw and citrus branches with different ratios (1:1, 3:1, 5:1, and 7:1) and the second plan included the production of biochar using compost obtained from the first design with rice straw and citrus branches with different ratios (1:1, 3:1, 5:1, and 7:1). Then, the amount of total lead, nickel and cadmium (digestion with nitric acid and perchloric acid) and available (extraction with DTPA) were measured in biochar and sewage sludge compost samples. Results and Discussion: Based on the results, the treatment of compost obtained from the combination of sewage sludge + rice straw in the ratio (1:1) reduced the amount of lead and total cadmium by 37.12 and 69.29%, respectively, compared to the control (sewage sludge). This reduction in the amount of lead and cadmium in the mentioned treatment is due to the high amount of rice straw compared to other treatments of rice straw and the greater degradability of rice straw compared to the citrus branch. The amount of available nickel in the treatments of compost + rice straw (1:1), compost + citrus branch (1:1), and (1:3) decreased by 46.12, 48.71, and 25.03%, respectively, compared to the control (sewage sludge). Also, the amount of available cadmium in compost treatments with rice straw (1:1), citrus branch (1:1), and (1:3) decreased by 43.97%, 33.18%, and 47.44%, respectively, compared to the control. Biochar had a significant effect on the amount of total lead and cadmium, so that the lowest amount of total lead and cadmium was observed in biochar + rice straw with a ratio of 1:1 and the amount of total lead and cadmium in this treatment decreased by 46.99 and 25.26%, respectively, compared to the control. Production of biochar from sewage sludge compost increased the amount of total lead and cadmium. However, the conversion of sewage sludge compost into biochar caused a significant decrease in the amount of available lead, nickel, and cadmium. Rice straw and citrus branches in biochar had no significant effect on available nickel. Conclusion: The production of compost and biochar from sewage sludge had a significant effect on the total and available heavy elements in the sludge. Therefore, in order to reduce the availability of lead, nickel, and cadmium, using the biochar method is preferable to compost and is prioritized. If the production of biochar is not cost-effective, the plant compounds of rice straw and citrus branches can be used in the production of sewage sludge compost, which has a significant effect on the immobilization of available heavy elements. Sewage sludge compost with rice straw by a ratio of 1:1, which has the lowest amount of pollution and the lowest cost for production, was recommended as the optimal treatment.